2014
DOI: 10.5897/ajest2013.1540
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals concentration in various tissues of two freshwater fishes, Labeo rohita and Channa striatus

Abstract: Heavy metals like cadmium, zinc, copper, chromium, lead and mercury were measured in the various tissues of Labeo rohita and Channa striatus and in the water samples collected from the Kolleru Lake, Andhra Pradesh during 2009-2010. The concentrations of heavy metals in the different organs of fishes varied. In L. rohita, the concentrations of heavy metals were in the order of liver > kidney > gills > muscles and in C. striatus, it was liver > kidney > gills > muscle. The values of heavy metals concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…It has been reported that the accumulation of heavy metals in gills is because of its thinnest epithelium among all the organs of the body through which metals can easily pass [27]. Mastan [21] has also been reported the similar pattern of bioaccumulation in Labeo rohita . Experimental studies have shown that muscles of Labeo rohita accumulate least metal zinc as compared to other organs [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the accumulation of heavy metals in gills is because of its thinnest epithelium among all the organs of the body through which metals can easily pass [27]. Mastan [21] has also been reported the similar pattern of bioaccumulation in Labeo rohita . Experimental studies have shown that muscles of Labeo rohita accumulate least metal zinc as compared to other organs [33].…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals deteriorate the ecological balance of the aquatic environment [1, 1921]. Because fishes are at the end of aquatic trophic level they have higher tendency to accumulate heavy metals in their body (Jakimiska et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The highest bioaccumulation of heavy metals in gills as reported in several studies could be attributed to two main reasons. First, because of its thinnest epithelium among all the organs of the body through which metals can easily pass (Mastan, 2014) and second, the surfaces of the gills are negatively charged whereas, the metal ions are positive charges due to which there is high affinity to the bonding between them (Siraj et al, 2016. The bioaccumulation of heavy metals in the freshwater fish muscles is especially of concern because these are rich protein sources and are vastly consumed as human food (Tunçsoy et al, 2016). As indicated by the results, the present study infers the accumulation of the lowest amount of lead in the muscles compared to the other organs, and several studies report the same.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals like Copper, Lead, Mercury, Cadmium, Nickel and Chromium are mainly responsible for water pollution. Heavy metal contamination may cause devastating effects on the ecological balance of the recipient environment and its diversity of aquatic organisms (Mastan, 2014). Metals have the tendency to accumulate in various organs of the aquatic organisms, especially fish, which in turn may enter into the human metabolism through consumption causing serious health hazards (Yousafzai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%